Ketahanan Pangan Rumahtangga Petani Padi di Desa Tambak Danau Kecamatan Astambul Kabupaten Banjar - Muhammad Faisal; Kamiliah Wilda; Umi Salawati (AGRIDES: Jurnal Agribisnis Perdesaan, 2013)
The study is purposed to analyze: (1) staple food security of rice farmer household. and (2) the obstacles encountered by farmers at study site. The study analyzes the food security level based on food availability, access and food use components. The results are described as follow. Based on staple food availability components, the total staple food production {husked rice) fulfills the daily need of land-owned farmers. The food access components also meet the food security requirement. based on the criteria of monthly family income, household head education. and the lighting availability. Furthermore, the households member characteristics also meet the food use component, as they have open access to drinking water (less than 100 m) and fresh water for sanitary (less than 100 m). health facility (100% used), and have educated housewife (90% of the housewives are primary school graduated). Overall, the land-owner farmer's households are food secured. The main problem encountered is the capability of farmers to diversify their income resources is weak. The farmers only rely on rice farming as income resource. Under the lower rice price and the living cost increase, their food security is fragile. The more frequent flood, which disturbs farm activities and yields, exacerbate their fragility. In addition, the knowledge of marketing is low, so farmers often act as price taker and accept whatever price offered by middleman buyer.